Factors Associated with Residual Symptoms of COVID-19 Virus at Infection among Health Care Personnel Roi Et Hospital - Sinthununsakul, Nantaka (Srinagarind Medical Journal, 2023)
Background and Objective: The symptoms of post COVID-19 infection often persist for several weeks after infection. The objective of this study was to investigate the factors associated with post symptoms after COVID-19 infection at a among health care personnel Roi Et hospital. Methods: This study was cross-sectional analytical study. Data were collected from 770 staffs of Roi Et Hospital who were infected with COVID-19 between July 2021 and June 2022. Data were analyzed using descriptive statistics, univariate analysis and multiple logistic regressions. The statistically significant was set at p<0.05. Results: Of 770 stuffs were infected with COVID-19, most of them (76.36%) were female mean age was 37.13± 9.09 years. Most of the clinical symptoms at the time of infection were coughing 81.28 %, sore throat 80.05%, fever 67.03% and runny nose 61.19%. There were 603 stuffs with residual symptoms after COVID-19 infection. The majority symptoms were fatigue 81.92%, coughing 41.29%, dyspnea 40.80%. Factors associated with long COVID-19 infection were male (Adj. OR= 2.53; 95%CI: 1.95-4.66), age > 50 (Adj. OR=2.78 95% CI: 1.64-5.18) Body Mass Index > 30 kg/m2 (Adj. OR=2.41; 95%CI: 1.46-4.32), underlying disease more than one (Adj. OR=1.89; 95% CI: 1.10-4.80). The clinical factor more than one symptom (Adj. OR= 2.45; 95%CI: 1.11-3.53), cough (Adj. OR=1.26; 95%CI1.17- 2.68), sore throat (Adj. OR=1.63; 95%CI: 1.06-2.51), and dyspnea (Adj. OR=1.58; 95% CI: 1.01-3.08). Conclusion: This study found that the factors associated with long COVID-19 infection among staffs of Roi Et hospital were male, age > 50 years, overweight class 1 or more, had at least one underlying disease, especially those had at least one clinical symptom and who had cough, sore throat, and dyspnea.